NGUSABA DODOL SEBAGAI REPRESENTASI BUDAYA AGRARIS DAN SOLIDARITAS MASYARAKAT KOMUNAL DI DESA ADAT DUDA, KARANGASEM - Ni Ketut Ayu Trisna Dewi (Yayasan Pendidikan Literasi Borneo, 2026)
The Ngusaba Dodol tradition is a Balinese tradition still preserved by the people of Duda Traditional Village, Karangasem Regency. This tradition not only has religious significance but also reflects the agrarian culture and communal solidarity of the indigenous community. However, amidst the development of modernization, the existence of local traditions faces various challenges, making it important to examine them as an effort to preserve culture. This study aims to analyze the Ngusaba Dodol tradition as a representation of the agrarian culture and communal solidarity of the Duda Traditional Village community. This study uses a qualitative approach with ethnographic methods. This approach is used to deeply understand the meaning of the Ngusaba Dodol tradition in the lives of the Duda Traditional Village community, Karangasem Regency. The results show that the Ngusaba Dodol tradition represents the community's agrarian culture through the use of agricultural products as a means of ceremony and the implementation of rituals as a form of gratitude for the harvest. Furthermore, this tradition also reflects communal solidarity through community involvement in mutual cooperation and cooperation during ceremonies. Thus, the Ngusaba Dodol tradition serves not only as a traditional ritual but also as a means of cultural preservation and strengthening social relations within indigenous communities.